2015
DOI: 10.1097/ccm.0000000000001138
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Transfusion of Circulation-Derived CD34+ Cells Improves Left Ventricular Function in Patients With End-Stage Diffuse Coronary Artery Disease Unsuitable for Coronary Intervention*

Abstract: CD34+ cell therapy was safe and efficacious in improving heart function for patients with severe diffuse coronary artery disease unsuitable for coronary intervention and with poor response to pharmacotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
110
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(140 citation statements)
references
References 18 publications
28
110
1
Order By: Relevance
“…These findings highlighted that not only the number of EPCs in circulation but also integrity of the endothelial function and capacity of endothelial-cell repairmen/renew were substantially weakened in CKD patients. Interestingly, our recent study has shown that the circulating levels of EPCs and the angiogenesis ability in both in-vitro and angiographic studies were significantly reduced in patients with diffuse coronary artery disease (CAD) [39]. Therefore, the conclusions reached in our recent study [39] corroborated the findings in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings highlighted that not only the number of EPCs in circulation but also integrity of the endothelial function and capacity of endothelial-cell repairmen/renew were substantially weakened in CKD patients. Interestingly, our recent study has shown that the circulating levels of EPCs and the angiogenesis ability in both in-vitro and angiographic studies were significantly reduced in patients with diffuse coronary artery disease (CAD) [39]. Therefore, the conclusions reached in our recent study [39] corroborated the findings in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, our recent study has shown that the circulating levels of EPCs and the angiogenesis ability in both in-vitro and angiographic studies were significantly reduced in patients with diffuse coronary artery disease (CAD) [39]. Therefore, the conclusions reached in our recent study [39] corroborated the findings in the present study. Importantly, the finding of our recent study [39] demonstrated that peripheral blood-derived CD34+ cell therapy significantly improved angina, heart failure and left ventricular function, supporting our hypothesis that CD34+ cell therapy might be beneficial to CKD patients with endothelial cell dysfunction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Clinical trials using G-CSF mobilized stem and progenitor cells have led to inconsistent data. Several studies showed significant therapeutic effects after intramyocardial or intracoronary injection of PB-derived MNCs [131-134] and CD34 + [135][136][137][138][139][140][141][142][143][144], whereas others did not detect functional differences between SC-treated and control groups [72,145,146]. Nevertheless, recently published data suggested that low circulating stem and progenitor cell counts are associated with minor heart function improvement after MI [99] and contribute to the development and progression of heart failure (HF) [147].…”
Section: Mobilized Stem and Progenitor Cellsmentioning
confidence: 99%